An ER‐directed transcriptional response to unfolded protein stress in the absence of conserved sensor‐transducer proteins in Giardia lamblia. Issue 4 (26th April 2013) - Spycher, Cornelia; Herman, Emily K.; Morf, Laura; Qi, Weihong; Rehrauer, Hubert; Aquino Fournier, Catharine; Dacks, Joel B.; Hehl, Adrian B.
Summary The protozoan Giardia lamblia has a minimized organelle repertoire, and most strikingly lacks a classical stacked Golgi apparatus. Nevertheless, Giardia trophozoites constitutively secrete variant surface proteins, and dramatically increase the volume of protein secretion during differentiation to cysts. Eukaryotic cells have evolved an elaborate system for quality control (QC) of protein folding and capacity in the endoplasmic reticulum (ER). Upon ER‐overload, an unfolded protein response (UPR) is triggered on transcriptional/translational level aiming at alleviating ER stress. In Giardia, a minimized secretory machinery and absence of glycan‐dependent QC suggests that a genetically conserved UPR (or functional equivalent) to cope with insults to the secretory system has been eliminated. We tested this hypothesis of UPR elimination by profiling the transcriptional response during induced ER‐folding stress. We show that on the contrary, ER‐folding stress triggers a stressor‐specific, ER‐directed response with upregulation of only ∼ 30 genes, with different kinetics and scope compared with the UPR of other eukaryotes. Computational genomics revealed conserved cis‐acting motifs in upstream regions of responder genes capable of stressor‐specific gene regulation in transfected cells. Interestingly, the sensors/transducers of folding stress, well conserved in model eukaryotes, are absent in Giardia suggesting the presence of a novel version of this essential eukaryotic function.